Novos caminhos para o enfrentamento do fracasso escolar?: a teoria e a prática no contexto da proposta escola plural - Mello, Flávia Carvalho Malta de (2001)
The present work is part of an investigative effort conducted under the supervision of the Center for Research and Studies of School Learning and Practices of the Graduate (Master’s Degree Levei) program (Department of Education - Federal University of Uberlândia). More specifically, this research focusses on issues related to the field of educational policies and their impact on institutional education. Its central objective was to discuss how the reality of school underachievement and failure has been addressed by politico-pedagogic proposals considered innovative. Most particularly it focuses on the Plural School (Escola Plural) model developed by the public school system of the city of Belo Horizonte in the mid 1990’s. It was necessary to understand to what extent the new approach adopted by the educational policies implemented in conjunction with the Escola Plural model created change in the “doing” and “thinking” in the art of teaching. To answer these questions it was necessary, in the beginning, to address the main theoretical approaches that deal with the issue of school underachievement and ftnd out how these approaches are present in the historical development of the Brazilian socitey and education. The starting point of the effort to address these issues was the “Movement for the New School”in Brasil, a movement that started in the 1920’s and culminating in the 1990’s with the advent of several alternative pedagogic approaches which were implemented in many public school Systems amongst which that of the city of Belo Horizonte. This data is systematized in the fírst chapter. The second chapter is dedicated to an analysis of the Escola Plural concept. Its goal is to analyse this new model, which was developed in contrast with and as an alternative to the traditional school model of selection and exclusion. The new model was conceived and developed based on new initiatives that were already emerging in the public school system of Belo Horizonte which sought to re-think pedagogic practices and examine methods dealing with the issue of school underachievement. Finally in the third chapter the data obtained from interviews with teachers of the Belo Horizonte public school system is properly categorized and systematized. Altogether 12 teachers participated in the interview process from a total of four (4) different schools. Two (2) of these schools were considered as resistant to the the Plural School model whereas the other two (2) were considered supportive of the model. In order to appropriately analyze, decode and process the data collected by way of these interviews, the theory of social representation was employed (with an approach delineated by Serge Moscovici). At the end of these analysis it was possible to establish that, despile proposing new mechanisms and new methodologies to deal with the issue of school underachievement, many elements of this new approach still relain influence of the biopsychological perspective as well as of the cultural déficit approach in their teaching practices and representations. The conclusion is that important changes have been achieved in the Belo Horizonte Public School System as a result of the Escola Plural model to overcome practices responsible for school underachievement. However, many of these changes have yet to be fully incorporated to the “doing” and “thinking” of the teaching practices of the professionals of the public school system.